2019
DOI: 10.1530/eje-19-0469
|View full text |Cite
|
Sign up to set email alerts
|

Association of adrenal insufficiency with patient-oriented health-care outcomes in adult medical inpatients

Abstract: Objective Adrenal insufficiency in the outpatient setting is associated with excess morbidity, mortality, and impaired quality of life. Evidence on its health-care burden in medical inpatients is scarce. The aim of this study was to assess the health-care burden of primary adrenal insufficiency (PAI) and secondary adrenal insufficiency (SAI) among hospitalized inpatients. Design and methods In this nationwide cohort study, adult medical patients with either PAI or SAI hospitalized between 2011 and 2015 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 30 publications
2
23
0
Order By: Relevance
“…Patients with hypopituitarism and concurrent secondary adrenal insufficiency may be at a greater risk of developing episodes of adrenal crisis. This may prompt visits to the ED, which then subsequently drive up the ED costs [30]. However, we found that the ED costs for patients with acromegaly and hypopituitarism were not higher than for those without hypopituitarism.…”
Section: Accepted Manuscriptmentioning
confidence: 67%
“…Patients with hypopituitarism and concurrent secondary adrenal insufficiency may be at a greater risk of developing episodes of adrenal crisis. This may prompt visits to the ED, which then subsequently drive up the ED costs [30]. However, we found that the ED costs for patients with acromegaly and hypopituitarism were not higher than for those without hypopituitarism.…”
Section: Accepted Manuscriptmentioning
confidence: 67%
“…In patients with adrenal insufficiency mortality rate appears to be more than doubled as compared to normal population, mainly due to cardiovascular disease and infections [ 121 ], particularly respiratory, which can be serious and expose to increased risk of hospitalization [ 122 ] and ICU admission [ 123 ] due to altered immune responses with reduced cytotoxic function of NK cells [ 124 ]. Clearly, increase in hospital admissions for such patients could also depend on a greater awareness of the risk of adrenal crisis during an infection [ 125 , 126 ].…”
Section: Pituitary Conditions and Covid-19mentioning
confidence: 99%
“…14 Higher rates of hypertension, renal insufficiency, COPD and cancer and higher CCIs were present in patients with AI in a previous retrospective study. 5 The higher prevalence of comorbid conditions in patients with AI has been attributed to long-term excessive glucocorticoid exposure. 4 Previous reports have stated that comorbidities are the most influential factor in determining the incidence of future adrenal crisis, which accounts for a quarter of hospital admissions in patients with AI.…”
Section: Comorbidities and Charlson Comorbidity Index In Readmissionsmentioning
confidence: 99%
“…Obesity and AI have been linked because long-term excesses of glucocorticoids in patients with adrenal insufficiency increase the risk of developing obesity. 5 Obesity and AI have also been associated through a POMC mutation. 19,20 POMC is a pro-peptide that is expressed in the immune system, skin, pituitary gland and hypothalamus.…”
Section: Ta B L E 2 Patient and Hospital Characteristics Of Hospitalizations With Adrenal Insufficiencymentioning
confidence: 99%
See 1 more Smart Citation